A mosasaur fauna (Squamata: Mosasauridae) from the Campanian (Upper Cretaceous) of Hannover, northern Germany. Issue 4 (2nd October 2018) - Hornung, Jahn J.; Reich, Mike; Frerichs, Udo
Abstract : Hornung, J.J., Reich, M. & Frerichs, U., February 2018. The mosasaur fauna (Squamata: Mosasauridae) from the Campanian (Upper Cretaceous) of Hannover, northern Germany. Alcheringa 42, 543-559. ISSN 0311-5518. Isolated teeth and a humerus from the Campanian of Hannover indicate a considerable local diversity of mosasaur taxa. The lower Misburg Formation (lower Campanian of the Lehrte West Syncline) yields Clidastes sp. (Mosasaurinae), Prognathodon sp. (Mosasaurinae), ? Hainosaurus sp. (Tylosaurinae) and an unidentified mosasaurid. It further confirms the presence of the genus Clidastes in northern central Europe and also proves the early Transatlantic distribution of a basal member of Prognathodon during the lower Campanian. ? Hainosaurus sp. is similar to roughly contemporaneous material of Hainosaurus sp. from southern Sweden. The upper Misburg Formation (upper upper Campanian) shows a different taxonomic composition with Tylosaurus sp. (Tylosaurinae), a second indeterminate species of Prognathodon and ? Platecarpus sp. The limited material of Prognathodon sp. shows closest affinities to P . lutugini (Yakovlev) from eastern Europe. The records of Tylosaurus and ? Platecarpus are among the stratigraphically youngest of these taxa. Facies and lithology of the Misburg Formation indicate that the mosasaurs lived in an open marine, mid-sublittoral environment with a water-depth around 70–100 m. In the contemporaneous chalk facies, deposited in somewhat deeper waters, as well as in shallow littoral deposits, mosasaurs are very rare and of lower diversity. Jahn J . Hornung [ jahn.hornung@yahoo.de ] Landesmuseum Hannover, Willy-Brandt-Allee 5, 30169 Hannover, Germany; Current address: Fuhlsbüttler Strasse 611, 22337 Hamburg, Germany; Mike Reich [ mreich@lrz.uni-muenchen.de & mike.reich@lmu.de ] SNSB—Bavarian State Collection of Palaeontology and Geology & Ludwig-Maximilian-Universität München, Department of Earth and Environmental Sciences, Section Palaeontology and Geobiology & GeoBio-Center LMU ; all: Richard-Wagner-Str. 10, 80333 Munich, Germany; Udo Frerichs [ udofrerichs@web.de ] Arbeitskreis Paläontologie Hannover, Buchenweg 7, 30855 Langenhagen, Germany